Awareness, knowledge and prevention of mother to child transmission of human immunodeficiency virus in pregnant women: a descriptive study - Parmar, Monika; Aherwar, Rupa; Jawade, Shashikala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India has the third highest number of estimated people living with HIV in the world. According to the HIV estimations 2012, the estimated number of people living with HIV/AIDS in India was 20.89 lakh, with an estimated adult (15-49 age group) HIV prevalence of 0.27% in 2011. The objective of this study was to evaluate the awareness and knowledge of mother-to-child transmission of HIV and its prevention among pregnant women attending the antenatal clinic. Methods: A cross sectional descriptive study was carried out at the antenatal clinic of Chirayu medical college and hospital, Bhopal, Madhya Pradesh, India from August 2015 to January 2016. Antenatal clinics run with average total attendance of 40 per day. A pretested questionnaire was designed to assess awareness of the women about HIV/AIDS, evaluate their knowledge of possible routes of transmission-particularly mother to child transmission-and measures to prevent vertical transmission from mother to child. Results: Amongst the respondents, 84% had heard of HIV and in 79% of them, the source of information was through mass media. 54.8% were aware of sexual intercourse as a mode of transmission of HIV while 43% knew that sharing sharp objects and infected blood products can spread HIV. 66% of respondents were aware of MTCT and 33.6% heard of antiretroviral therapy as a method of prevention of MTCT. 74% were aware of contracting infection by sexual contact with infected partner. Majority of them (77.4%) were aware of increased risk of contracting HIV/AIDS by sexual relationship with multiple partners. 74% of females were aware that HIV/AIDS is preventable. 59.6% of women were aware of availability of ART of AIDS treatment. 72.5% of study population was aware that use of condom can protect against HIV transmission. Conclusions: Although awareness of HIV and MTCT is increased as compared to previous studies, but to achieve global plan to reduce MTCT by 90% there is still need to promote programs targeting antenatal population with emphasis on MTCT and its various methods of prevention.